Infonavit WUF9 / Kuala Lumpur 2018 (ONU Hábitat Infonavit, 2018)
UN-Habitat estimates that in 2014 there was 881 million people living in slums in developing country cities. This represents an increase of 28% over the past 24 years. Still, in 2014, 30 % of urban population of developing countries resided in slums, compared to 39 % in the year 2000.